Pengaruh Harga dan Promosi di Media Sosial terhadap Keputusan Konsumen Membeli MH Whitening Skin di Makassar - Kapriani, Kapriani; Jusman, Ikhsan Amar; Hardianti, Hardianti (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This research aims to determine the influence of price and promotions on social media on purchasing decisions for MH Whitening Skin. This research uses primary data and also secondary data. The research method used was incidental sampling with a sample size of 100 people. The data analysis techniques used are validity testing, reliability testing. Testing the analytical model in this research uses multiple linear regression analysis, T test, F test and R determination. Based on the results of research using the T test, it was found that price had a significant influence on purchasing decisions for MH Whitening Skin, as well as promotions on social media had a significant influence on purchasing decisions for MH Whitening Skin in Makassar. F test results: Price and promotion via social media simultaneously have a significant influence on purchasing decisions for MH Whitening Skin, where promotions on social media are the most dominant factors influencing purchasing decisions for MH Whitening Skin in Makassar.